Tytuły cesarskie w pismach Lucyfera z Cagliari - Wilk, Piotr (Vox Patrum, 2024)
The article presents what titles Lucifer of Cagliari applies to Emperor Constantius II. The main part of the work is preceded by a short introduction, which contains basic information about the Author and his works. The main part describes selected contexts of use of individual groups of titles and the functions they perform. The bishop used titles to express irony, show the ruler his error and persuade him to convert. The titles used for the monarch were also compared with those used for other people and with the titles used by Hilary of Poitiers for Constantius II. The article presents what titles Lucifer of Cagliari applies to Emperor Constantius II. The main part of the work is preceded by a short introduction, which contains basic information about the Author and his works. The main part describes selected contexts of use of individual groups of titles and the functions they perform. The bishop used titles to express irony, show the ruler his error and persuade him to convert. The titles used for the monarch were also compared with those used for other people and with the titles used by Hilary of Poitiers for Constantius II.